The use of cognitive screens within major trauma centres in England: A survey of current practice. (July 2020) - Teager, AJ; Methley, A; Dawson, B; Wilson, H
Introduction: Major trauma centres are effective in reducing morbidity and mortality rates following serious injury. Many patients attending major trauma centres present with traumatic brain injuries, requiring specialist assessment in screening for potential cognitive deficits. Numerous cognitive screens exist but it is currently unclear which are used most frequently within major trauma centres. This study aimed to identify which screening tools are used most frequently in major trauma centres in England to enable discussion around their suitability for this clinical population. Method: Electronic surveys were distributed via a mailing list to Clinical Psychologists and Clinical Neuropsychologists in major trauma centres across England to gather data on the use of cognitive screens. Results: Fourteen Clinical Psychologists in Neuropsychology participated. Results suggest major trauma centres in England are currently using the ACE-III (50%) or MoCA (42%) as the most frequently used screens for cognitive difficulties following traumatic brain injury. Cognitive screening pathways are multi-disciplinary involving OTs (86%), psychologists (qualified 79%; assistant 57%) psychiatrists (36%), mental health nurses (7%) and therapy assistants (7%). Conclusions: Major trauma centres are using evidence-based cognitive screens at present, but further work is needed to develop more effective, better validated cognitive screens for traumatic brain injury populations. Increased inter-professional discussion on the practice of cognitive screening would be beneficial for patients seen within major trauma centres.